Farm level potato (Solanum tuberosum l.) Cultivation in some selected sites of Bangladesh (Bangladesh Journal of Agricultural Research, 2013)
The study was carried out in two intensive potato growing areas (Rangpur and Munshigonj) to estimate the technical efficiency of potato producers and to describe the level of variation in potato productivity due to differences in input use. Data were collected from 60 farmers (30 farmers from each district) using simple random sampling technique. Average technical efficiency was 86% implying that on average 14% inefficiency remained at producers level. The application of human labour, MoP, and weedicides would increase potato yield significantly. On the other hand, the coefficient of urea and pesticide cost was found negative and significant which advarsely effect the yield of potato. Moreover, the coefficient of operated land and extension linkage were found negative and significant implying that with further increase in operated land and extension linkage, technical efficiency would increase. Munshigonj was found to be more suitable area for potato production. The performance of selfproduced and stored potato seeds are poor compared to the seeds from BADC. Supply of quality seeds to the farmers should be ensured by strengthening seed production and distribution system both in public and private sectors. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16972 Bangladesh J. Agril. Res. 38(3): 455-466, September 2013